Protocolo de avaliação da intervenção do psicólogo hospitalar: uma contribuição para a sistematização da prática do psicólogo em ambientes médicos - Leite, Luiz Gonzaga (2007)
Because of the need to promote the systematization for the psychologist's practice in a medical environment, this study s main objective was to investigate through the Protocol for the Evaluation of the Intervention by the Hospital s Psychologist, the normalization between the hospitalized patient's demand and the psychological assistance served to the patient. For this purpose, 312 hospitalized patients of a private hospital from a certain county in São Paulo, of both sexes and ages ranging from 20 and 70 years old, participated by answering a questionnaire for identification, a resilience scale and a Protocol of Evaluation for the Clinical Psychologist's Intervention. The argumentations were applied by six psychologists from the psychology team of the hospital in question, whose author is the coordinator; with each receiving adequate training when collecting and assisting the study's participants. Those who accepted to participate in the research, signed the Term of Free and Clarified Consentment elaborated in accordance to the determinations seen in the Resolution 196/96 from the National Health Group. In regards to the patient's demands and the type of assistance offered by the psychologist, the data collected revealed a difficulty experienced by the psychologist when choosing which patient really needed some type of intervention, since the groups considered to be more reserved according to its resilience level and its psychic and behavioral manifestation, received more care from the clinical psychologist in comparison to the other groups. After contemplating the analysis, it is plausible that the use of Evaluation Protocol of the Clinical Psychologist s Intervention can assist the clinical psychologist to collect the patient's data, since it allows him to identify the patient's condition in regards to the protective factors that are characteristic of their resilience and consequently allowing a more adequate psychological assistance to the demand presented to the patient. We believe the Evaluation Protocol for the Clinical Psychologist's Intervention presented in this study allows an important contribution for the discussion about the necessity to systematize the psychologist's practice in the clinical environment. Our commitment to improve the results gathered in this study has been strengthened, aiming to broaden the contributions for the systematization for the psychologist's practice in a medical environment